Pembelajaran IPA Berbasis Pendidikan Karakter dengan Huruf Braille untuk Siswa Difable Netra - Yulizah, Yosi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
One of the goals of national education is the effort to form children's character. Without exception, children who have a good sense of sight, both of whom cannot function properly, are called blind people with disabilities and also need good character education as an effort to develop the potentials that exist within them optimally and optimally. Natural education science is one of the subjects that also requires the development of character education. The data collection method uses library research, with a qualitative approach and the data source is secondary data. Furthermore, the data analysis technique is by managing data (reduction), data display, and conclusions from the final results of data collection carried out. The results of this study obtained a clear explanation of: A. Character education, B. Characteristics of science studies, C. Science learning, D. Science learning objectives, E. Children with special needs, F. Braille, G. Implementation of education-based science learning Braille characters for blind students can be implemented in three stages, including: 1). Planning consists of formulating learning objectives, selecting and packaging materials by incorporating character education values into the lesson plans; 2). Implementation consists of science subjects and integration with other subjects; 3). Evaluation consists of assessment activities based on the application of character education values that are implemented on the attitudes and behavior of students with visual impairments in schools.